Beyond the spotlight: Unveiling the gender bias curtain in movie reviews - Jad Doughman; Wael Khreich (PLoS ONE, 2025)
Historically, the film industry has been male-dominated both in front of and behind the camera, resulting in a longstanding gender imbalance in storytelling and representation. This legacy of male-centric narratives may unconsciously influence critics’ expectations and judgments. Existing literature suggests that negative critiques in movie reviews can significantly impact actors’ earnings by diminishing a film’s commercial prospects. This influence extends to potential reductions in back-end compensation and marketability for future projects, and it can directly affect actors’ well-being, leading to increased stress levels and elevated cardiovascular reactivity. Previously, gender biases in movie reviews were computed using disparities in male-led versus female-led movie ratings or box-office earnings; however, no work has been done to quantify the linguistic biases within movie review transcripts. This work aims to leverage our language-model-powered gender bias detection system to measure benevolent sexism, hostile sexism, explicit marking of sex, dehumanization, and generic pronouns in reviews published by professional critics. Therefore, we analyzed 17,165 professionally written reviews, comprising a total of 735,000 sentences. Our analysis uncovers pronounced representation bias in key movie roles, with 72% of first actors, 91% of first directors, and 86% of first writers being male. More importantly, the findings indicate that movies with female-dominated casts evoke, on average, 149% higher magnitude of hostile sexism and 44% higher magnitude of benevolent sexism in their reviews compared to movies with male-dominated casts. We also find that benevolent sexism is most common in Family and Music genres, reflecting the romanticization of gender roles, whereas hostile sexism peaks in Romance. A non-parametric statistical analysis revealed significant gender differences in benevolent and hostile sexism scores for movie reviews, with female first actors, directors, and writers receiving higher levels of both benevolent and hostile sexist criticism compared to their male counterparts.